Oxygen vacancy rich Cu2O based composite material with nitrogen doped carbon as matrix for photocatalytic H2 production and organic pollutant removal. Issue 6 (19th January 2018) - Lu, Lele; Xu, Xinxin; Yan, Jiaming; Shi, Fa-Nian; Huo, Yuqiu
Abstract : A new strategy was explored to obtain oxygen vacancy rich Cu2 O based photocatalyst with nitrogen doped carbon as the matrix through the calcination of coordination polymer precursor. Abstract : A nitrogen doped carbon matrix supported Cu2 O composite material (Cu/Cu2 O@NC ) was fabricated successfully with a coordination polymer as precursor through calcination. In this composite material, Cu2 O particles with a size of about 6–10 nm were dispersed evenly in the nitrogen doped carbon matrix. After calcination, some coordinated nitrogen atoms were doped in the lattice of Cu2 O and replace oxygen atoms, thus generating a large number of oxygen vacancies. InCu/Cu2 O@NC, the existence of oxygen vacancies has been confirmed by electron spin resonance (ESR) and X-ray photoelectron spectroscopy (XPS). Under visible light irradiation, Cu/Cu2 O@NC exhibits excellent H2 production with the rate of 379.6 μmol h −1 g −1 . Its photocatalytic activity affects organic dyes, such as Rhodamine B (RhB) and methyl orange (MO). In addition to photocatalysis, Cu/Cu2 O@NC also exhibits striking catalytic activity in reductive conversion of 4-nitrophenol to 4-aminophenol with in presence of sodium borohydride (NaBH4 ). The conversion efficiency reaches almost 100% in 250 s with the quantity ofCu/Cu2 O@NC as low as 5 mg. The outstanding H2 production and organic pollutants removal are attributed to the oxygen vacancy. We expect thatCu/Cu2 O@NC will find its way as a new resource for hydrogen energy as well as a promising material in water purification.